On Some Growth Relations of Composite Integral Functions Represented By Central Index - Aseel Hameed Abedsadaa (Al-Mustansiriyah Journal of Science)
In the present paper, the growth rate of the central index of the composition of two integral functions in terms of the left and right factors are discussed.